GE_GERICHTE P/14351/2017 vom 16. Juni 2022 - GE Cour de justice (2022)
AGRESSION;LÉSION CORPORELLE SIMPLE;MENACE(DROIT PÉNAL);CONCOURS D'INFRACTIONS;FIXATION DE LA PEINE;EXPULSION(DROIT PÉNAL);TORT MORAL;COAUTEUR(DROIT PÉNAL) | CP.134; CP.123.al1.ch2; CP.181; CP.66.al1; CP.66bis.leta; CPP.122.al1; CPP.135.al1